Hierarchical porous carbon nanosheets derived from rice husk as coating layer for the anode of lead-carbon battery - Venkatachalam, Priyadarshini; Murugan, Nagaraj; Dhanabalan, Karmegam; Kang, Min; Choi, Yu Rim; Youn, Seung Hwi; Noh, Seon Yeong; Hong, Seungki; Muramatsu, Hiroyuki; Jung, Ho-Young; Kim, Yoong Ahm (Elsevier BV, 2025)
Biomass-derived porous carbons offer a sustainable and cost-effective strategy to enhance the performance of lead-carbon batteries (LCBs), but challenges remain in controlling surface chemistry and suppressing the hydrogen evolution reaction (HER). In this study, we introduce a dual modification approach for rice husk-derived activated carbon (RHAC), involving thermal treatment at 1000 degrees C followed by nitrogen functionalization via amination, to produce a surface-engineered material designated as HTT-N. Unlike conventional additive mixing, HTT-N is applied as a thin coating layer on the negative electrode to improve interfacial stability and redox efficiency. The HTT-N carbon retains a hierarchical porous structure and exhibits partial graphitic ordering, high electrical conductivity, and a nitrogen content of 2.08 wt%. These features collectively contribute to accelerated Pb/PbSO4 redox kinetics, enhanced charge transport, and effective HER suppression. Electrochemical tests reveal a high specific discharge capacity of 1.89 Ah g- 1 and outstanding cycling durability exceeding 40,000 cycles under high-rate partial-state-of-charge (HR-PSOC) conditions. These findings